N6-methyladenine RNA methylation epigenetic modification and diabetic microvascular complications - Wang, Yuanyuan; Zou, Jiayun; Zhou, Hua (Frontiers in Endocrinology, 2024)
N6-methyladensine (m6A) has been identified as the best-characterized and the most abundant mRNA modification in eukaryotes. It can be dynamically regulated, removed, and recognized by its specific cellular components (respectively called “writers,” “erasers,” “readers”) and have become a hot research field in a variety of biological processes and diseases. Currently, the underlying molecular mechanisms of m6A epigenetic modification in diabetes mellitus (DM) and diabetic microvascular complications have not been extensively clarified. In this review, we focus on the effects and possible mechanisms of m6A as possible potential biomarkers and therapeutic targets in the treatment of DM and diabetic microvascular complications.